2022
DOI: 10.3389/fonc.2022.932637
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy in Oligometastatic, Oligorecurrent and Oligoprogressive Prostate Cancer: A Mini-Review

Abstract: Globally, prostate cancer is one of the most common malignancies affecting men. With the advent of advanced molecular imaging, an increasing number of men are found to have oligometastatic disease (OD) either at primary diagnosis or at the time of biochemical failure. No strict definition exists for OD, with historical and ongoing studies utilizing diverse criteria. There is mounting evidence from many different malignancies that patients with OD have improved outcomes compared to their widely metastatic count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Immune checkpoint inhibitor therapies were also examined with limited success 67 , 68 . Ongoing studies examine these therapies in combination with radiotherapy 69 71 .…”
Section: Resultsmentioning
confidence: 99%
“…Immune checkpoint inhibitor therapies were also examined with limited success 67 , 68 . Ongoing studies examine these therapies in combination with radiotherapy 69 71 .…”
Section: Resultsmentioning
confidence: 99%
“…The adrenal gland is a common site of metastases from many malignancies [ 103 ] and the indications have been increasing for a definitive treatment in metastatic adrenal lesions [ 104 , 105 ]. There was insufficient evidence to determine the best local treatment modality for isolated and limited adrenal metastases [ 106 ].…”
Section: Smart Clinical Applicationsmentioning
confidence: 99%
“…SBRT for oligoprogression has been evaluated in a limited number of settings. In prostate cancer, retrospective cohort studies have demonstrated that radiotherapy can prolong next-line systemic therapy-free survival (NEST-FS) and progression-free survival (PFS) among at least a subset of patients with oligoprogression [5]. A retrospective analysis similarly found that SBRT may have the potential to extend the duration of current systemic therapies among patients with renal cell carcinoma [6].…”
Section: Introductionmentioning
confidence: 99%
“…This could preserve subsequent treatments for later administration and, therefore, enable a longer total duration of treatment and possibly even a longer survival time [6]. However, even among disease sites that have been investigated, there remains a paucity of prospective data on the effectiveness of radiotherapy in treating oligoprogression [5,6]. Recently, a prospective phase II trial was carried out among patients with renal cell cancer receiving SBRT and tyrosine kinase inhibitor (TKI) therapy [7].…”
Section: Introductionmentioning
confidence: 99%